Step-by-Step Regulation of Productive and Abortive Transcription Initiation by Pyrophosphorolysis. Issue 13 (15th July 2022) - Plaskon, Dylan; Evensen, Claire; Henderson, Kate; Palatnik, Benjamin; Ishikuri, Takahiro; Wang, Hao-Che; Doughty, Sarah; Thomas Record Jr., M.
Graphical abstract: Highlights: Time for productive initiation is greatly increased by physiological [PPi]. Amount of productive initiation is greatly reduced by physiological [PPi]. Amount of nonproductive initiation is greatly increased by physiological [PPi]. Pyrophosphorolysis in initiation is highly sequence-dependent. Pyrophosphorolysis effects in initiation are much larger than in elongation. Abstract: An understanding of the kinetics and mechanism of bacterial transcription initiation is needed to understand regulation of gene expression and advance fields from antibiotic discovery to promoter design. The step-by-step forward kinetics and mechanism of initiation and RNA-DNA hybrid growth, made irreversible by omitting pyrophosphate (PPi) byproduct, were determined recently for E. coli RNA polymerase (RNAP)-λPR promoter complexes. Strong position-dependences of overall rate constants (kcat /Km analogs) for each nucleotide-addition step were observed because of coupling of hybrid growth to disruption of promoter contacts, bubble closing, and RNAP escape. Here we investigate reversal of these steps (pyrophosphorolysis) at PPi concentrations ([PPi]) found in exponentially-growing cells. We quantify [PPi] effects on the amount and rate of synthesis of long (>10-mer, post-escape) and short (stalled, abortive) RNA to determine how PPi regulates initiation. Physiological [PPi] makes uridine incorporation and some other initiation steps significantly reversible. Physiological [PPi] reduces the fraction of RNAP-promoter complexes that productively initiate and the rate of RNA synthesis per productive complex, while increasing the fraction of complexes that abortively initiate, affecting abortive rates, and shifting the abortive-product distribution to shorter RNAs. Pyrophosphorolysis rates for some initiation complexes are orders of magnitude larger than for removal of the same nucleotide from elongation complexes because of the strong bias toward the pre-translocated state in initiation, and exhibit even stronger dependences on nucleotide identity (pyrimidine ≫ purine). Because cytoplasmic [PPi] is much higher in exponential-phase than stationary-phase cells, these [PPi] effects on initiation rates and amounts of RNA synthesis must be physiologically-relevant.